2018
DOI: 10.1016/j.ijhydene.2018.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of laminar hydrogen/oxygen flames in a tube and the possible onset of detonation

Abstract: The possibility is analysed of a laminar flame accelerating along a cylindrical tube, closed at one end, and inducing a deflagration to detonation transition in a stoichiometric H2/O2 mixture. The pressure and temperature ratios at the ensuing shock wave increase, as do laminar burning velocities, while autoignition delay times decrease. Combined with appreciable elongation of the flame, these enhance the strength of the shock. The conditions necessary for delay times of 0.05, 0.1, 1.0 and 5.0 ms, at an unburn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Hydrogen and O2 can also be formed in light water cooled nuclear reactors by the radiolytic decomposition of water [7]. If significant amounts of H2 and O2 were to be created by radiolysis in stoichiometric proportions, this would be very serious because of the very high reactivity, and the potential for detonation, of such a mixture [8]. However, Gordon et al [9] found this not to be so, with no more than 0.7% H2 being created by radiolysis, which could be removed by recombination.…”
Section: General Considerationsmentioning
confidence: 99%
“…Hydrogen and O2 can also be formed in light water cooled nuclear reactors by the radiolytic decomposition of water [7]. If significant amounts of H2 and O2 were to be created by radiolysis in stoichiometric proportions, this would be very serious because of the very high reactivity, and the potential for detonation, of such a mixture [8]. However, Gordon et al [9] found this not to be so, with no more than 0.7% H2 being created by radiolysis, which could be removed by recombination.…”
Section: General Considerationsmentioning
confidence: 99%